Artificial Intelligence and Islamic Perspective in Student Character Assessment - Maskur, Said; Hasyamuddin bin Othman (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2025)
Artificial intelligence (AI) is increasingly adopted in higher education, including in student character assessment. However, AI’s inability to capture spiritual aspects such as intention (niyyah), sincerity, and God-consciousness (taqwa) creates a gap between technological efficiency and the moral values of Islamic education. This study aims to explore students’ perceptions of AI-based character assessments in Islamic universities and propose a conceptual framework grounded in maqasid al-shariah. A descriptive qualitative method with a phenomenological design was employed, involving 20 purposively selected students from five academic programs at the Ar-Risalah Institute of Islamic Studies, Riau. Data were gathered through in-depth interviews, observations, and document analysis, and analyzed using the Miles and Huberman model. The findings reveal students’ distrust toward AI’s fairness, particularly its failure to assess inner spiritual dimensions, and highlight the irreplaceable role of educators in moral guidance. The study concludes that AI should be ethically guided and embedded with Islamic values to ensure its compatibility with character education in faith-based institutions. A value-sensitive AI framework can help harmonize automation with spiritual integrity, allowing Islamic higher education to adopt digital technologies without compromising its sacred pedagogical mission.